Three new synonyms of Rhopalopsole sinensis Yang & Yang, 1993 (Plecoptera: Leuctridae) - Yang, Yu-Ben; Du, Yu-Zhou (Zootaxa, 2021)
We recently examined specimens of the Rhopalopsole from Hubei, Ningxia and Shaanxi, China and three new synonyms of Rhopalopsole sinensis Yang & Yang, 1993 are established: Rhopalopsole furcata Yang & Yang, 1994, Rhopalopsole hongpingana Sivec & Harper, 2008 and Rhopalopsole ningxiana Li & Yang, 2010 are synonymized with Rhopalopsole sinensis Yang & Yang, 1993. We also place Rhopalopsole furcospina (Wu, 1973) as a nomen dubium. Long hairs on the antennae of R. sinensis thought to be diagnostic also occur on Rhopalopsole ampulla Du & Qian, 2011, Rhopalopsole exiguspina Du & Qian, 2011, and Rhopalopsole memorabilis Qian & Du, 2014. We provide new images of several species to facilitate identification.